2019
DOI: 10.4314/ejst.v12i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of household dietary diversity in Yayu Biosphere Reserve, Southwest Ethiopia

Abstract: Lack of dietary diversity is a severe problem among the poor in the developing world, including Ethiopia. Empirical evidence for factors contributing to low dietary diversity hardly exists. The objective of this study was to analyze determinants of Household Dietary Diversity and consumption behavior in Yayu biosphere reserve, South-West Ethiopia. A cross sectional survey was conducted on 183 randomly selected households. Primary data were collected from sample households through interviews, focus group discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
6
10
2
Order By: Relevance
“…It has been reported that households headed by persons with no formal education lack understanding of nutrition [43] and the health benefits of a well-balanced diet. As a result, they are less likely to diversify their diet as compared to farmers with formal education [9,45]. Contrary to the findings of this study, Udoh and Udoh [50] reported that more than 80% of the households in their study consumed food from these groups.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…It has been reported that households headed by persons with no formal education lack understanding of nutrition [43] and the health benefits of a well-balanced diet. As a result, they are less likely to diversify their diet as compared to farmers with formal education [9,45]. Contrary to the findings of this study, Udoh and Udoh [50] reported that more than 80% of the households in their study consumed food from these groups.…”
Section: Discussioncontrasting
confidence: 90%
“…The dominance of cereals in the diets of the respondents in the present study was anticipated given that cereals, such as maize, are a common staple food throughout South Africa [43] and more so among emerging farmers [44]. Similar results were observed by Jebessa et al [45] who noted that the diet of the households in Yayu Biosphere Reserve, Ethiopia consisted mainly of cereals. While previous studies carried out in Tanzania and South Africa observed that only a few participants had consumed vegetables [9,43], over three-quarters of respondents in the present study indicated that they had consumed vegetables over the recall period.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It does so through its role in supporting more diversified production of crops including vegetables, fruits, and cash crops, compared to non-irrigating households [51]. [52] found that access to irrigation was among the most important determinants of household dietary diversity. This was supported by their finding in which dietary diversity of households with access to irrigation was higher by a factor of 5.824 than those households with no access to irrigation.…”
Section: Importance Of Irrigation To Food Security In Ethiopiamentioning
confidence: 99%